2020
DOI: 10.1039/d0ra00416b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface oxidation on the electronic transport properties of phosphorene gas sensors: a computational study

Abstract: Computational study of surface oxidation effects on phosphorene-based gas sensors, and potential for nM L−1 detection and measurement of nitrogen–oxygen moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
3
4
0
Order By: Relevance
“…Note that the adsorption energy of NO 2 on BP reported here is higher than that observed in some previous literature. , This is probably because oxygen-containing end groups were taken into consideration when building the BP model in this report. For one study in which the surface adsorption behavior of partially oxidized BP was investigated, the NO 2 adsorption energy (−0.81 eV) is close to the value obtained here . The adsorption behavior induced a local structural deformation in the NO 2 molecule, showing an increase in the N–O bond (away from F-BP basal plane) length from 1.21 to 1.26 Å and a decrease in the O–N–O band angle from 133.49° to 121.77°.…”
Section: Results and Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Note that the adsorption energy of NO 2 on BP reported here is higher than that observed in some previous literature. , This is probably because oxygen-containing end groups were taken into consideration when building the BP model in this report. For one study in which the surface adsorption behavior of partially oxidized BP was investigated, the NO 2 adsorption energy (−0.81 eV) is close to the value obtained here . The adsorption behavior induced a local structural deformation in the NO 2 molecule, showing an increase in the N–O bond (away from F-BP basal plane) length from 1.21 to 1.26 Å and a decrease in the O–N–O band angle from 133.49° to 121.77°.…”
Section: Results and Discussionsupporting
confidence: 76%
“…For one study in which the surface adsorption behavior of partially oxidized BP was investigated, the NO 2 adsorption energy (−0.81 eV) is close to the value obtained here. 39 The On the other hand, this adsorption process also caused significant charge transfer between NO 2 and the host materials.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophobic surface becomes hydrophilic due to the chemisorption of oxygen, which then promotes the production of phosphoric acids. , This degradation occurs on a pristine lattice only when the energy from the light is in the ultraviolet range but is reduced to the visible range on defect sites, including native single phosphorus vacancies. , Now, more surface-sensitive techniques have shown that phosphorus oxides can form on the pristine lattice from either oxygen or water alone . This degradation mechanism has been discussed in the theoretical literature, but there is not a consensus on how BP oxidation occurs and experimental studies so far have been limited to averaged effects of degradation over a micron- to millimeter-sized region rather than individual reaction sites. …”
Section: Introductionsupporting
confidence: 65%
“…However, all allotropic forms of phosphorus often present the significant drawback of air-instability. Such instability, particularly in the case of black phosphorus, is believed to be the result of slow oxidation in O 2 -rich and humid atmospheric conditions [8]. To construct any useful electronic device suited for molecular sensing, efforts must be made to stabilize the material without compromising its electronic properties.…”
Section: Introductionmentioning
confidence: 99%